(untitled) (Development Engineering Conferences Center Articles Database, 2024)
The development of effective and stable electrocatalysts for the oxygen evolution reaction (OER) in an alkaline environment , which can achieve high current density and low overpotential, is a critical challenge. In recent years, perovskite oxides have emerged as promising candidates for efficient OER electrocatalysts due to their versatile physicochemical properties. However, they face certain limitations that hinder their widespread adoption. One approach to improve the electrochemical performance of perovskite oxides is through partial doping of their B-site elements. In this study, we investigated the effect of partial chromium doping on LaCoO3 perovskite, resulting in the formation of LaCo0.5Cr0.5O3 . Our results revealed that this compound exhibited outstanding electrochemical activity, with an overpotential of 291.96 mV at a current density of 10 mA/cm2 and by remaining stable during 4 hours of testing. This improvement was attributed to the increased oxygen vacancy and porosity in the structure of LaCo0.5Cr0.5O3. This study demonstrates that partial substitution in perovskites is an effective means to improve their catalytic activity in the OER process. Furthermore, this strategy can be extended to other perovskite oxides with chromium incorporated into their B-site, potentially resulting in improved performance.